Managing the Master Planning Process: How do airport managers incorporate stakeholder contribution in their final master plans? - Dixon, Sally (Cranfield University, 2014)
This research seeks to connect the philosophical focus of the agency-structure debate with the practice of management through a comparative study of organisational decision-making in situations involving stakeholder consultation. Set in the context of decision-making following an airport master plan consultation, the study considers how the stakeholder framework can be integrated within institutional theory using institutional logics as a theoretical link between these two literatures. This thesis, which adopts a critical realist perspective, takes a comparative case approach of four airports, each owned in different ways. Interviews with airport managers are supplemented by discussions with stakeholders and industry experts. Two sets of a priori themes were identified from the literature. The first focuses on the institutional logics prevailing in the field and their influence on managers as they make decisions. The second considers four decision-making strategies managers might employ in this situation. Findings centre on the causal powers acting upon airport managers as they make their decisions. Whilst normative isomorphic pressure enables stakeholder consultation, the coercive pressure on the decision-making process deriving from English planning law, the adversarial and oscillating nature of Central Government policy, and a mimetic response to the nature of local authority development plans constrain the actions of airport managers. Indeed, the current bureaucratic form of capitalism limits stakeholder contribution to final master plans. This research makes four main contributions: Firstly, reflecting upon the agency-structure debate from a critical realist perspective has facilitated development of a model integrating the stakeholder framework within institutional theory. Secondly, it improves our understanding of how stakeholder contribution is managed in master planning. Thirdly, the study adds to the growing body of work that employs a critical realist perspective. Lastly, since reconciling conflicting stakeholder opinions may well be of vital importance to the future of the UK’s airport infrastructure, this work has practical significance for airport managers, government policy-makers and stakeholders as they strive to formulate worthwhile airport consultations.
Keywords: Agency-structure; airport master planning; bureaucratic capitalism; comparative case research; critical realism; decision-making; institutional logics; institutional theory; stakeholder consultation; stakeholder theory